Selenopentathionic and Telluropentathionic Acids as Precursors for Formation of Semiconducting Layers on the Surface of Polyamide - Skirma Zalenkiene; Judita Sukyte; Remigijus Ivanauskas; Vitalijus Janickis (International Journal of Photoenergy)
The layers of copper chalcogenides, which were formed on the surface of semihydrophilic polymer—polyamide 6 (PA) using monoselenopentathionic H2SeS4O6 and monotelluropentathionic H2TeS4O6 acids as precursors of chalcogens, were characterized. Fourier transform infrared (FT-IR) and UV spectroscopy were used to monitor the effect of chalcogens on the changes in structure of PA corresponding to the concentration of the precursor's solution and an exposure time. The IR spectra of modified PA were completely different from that of the initial PA. Further interaction of chalcogenized PA with copper (II/I) salt solution leads to the formation of CuxS, CuxSe, CuxTe, and mixed –CuxS–CuySe and CuxS–CuyTe layers which have different electric transport properties. The surface properties of PA after treatment are studied using AFM and XRD. The electrical resistances of layers with various composition formed over a wide concentration range 0.01–0.5 mol⋅dm−3 of precursor's solution were measured. Variation in the conductivity of layers of Cu–Se–S and Cu–Te–S on the surface of PA shows an evident increase with the increasing of the mass fraction of selenium or tellurium.